BRIDGING THE GAP: OPPORTUNITIES, CHALLENGES AND STRATEGIES FOR AI DEPLOYMENT IN PUBLIC SERVICE DELIVERY - Richard Douglas Kamara (Публічне управління та регіональний розвиток)
Artificial intelligence (AI) has the potential to revolutionise public service delivery, but its creation and implementation come with both exciting possibilities and complex obstacles. Despite the increasing discussions surrounding AI, there is a lack of research specifically focused on its implications within public service sectors, healthcare, education, and transportation. This paper aims to fill this gap by critically examining how AI can enhance efficiency, decision-making, and service accessibility while also exploring the hurdles posed by its implementation, including technical infrastructure requirements, workforce adaptation, ethical concerns, and governance complexities. By conducting a thorough analysis of existing research, the study uncovers significant opportunities, including enhanced accessibility, data-driven insights, and streamlined operations. At the same time, it emphasises significant challenges, such as algorithmic bias, data privacy risks, public trust deficits, and resource disparities that may impede the equitable adoption of AI. To tackle these obstacles and promote responsible AI deployment, this paper examines strategic approaches that encompass establishing transparent governance frameworks to ensure accountability, enhancing data privacy and security protocols to safeguard public information, and fostering AI literacy through comprehensive workforce training. Moreover, it seeks to echo the importance of ethical AI development aimed at addressing bias and fostering inclusivity, while ensuring that AI solutions are in line with societal requirements. Building scalable and inclusive AI infrastructure is crucial for closing the digital divide and guaranteeing fair access to AI-powered services, especially in marginalised communities. Additionally, building public trust by implementing transparent policies and actively involving citizens in the adoption process is vital for the successful integration of AI. Given the scarcity of research on AI’s impact on public service delivery, this paper offers valuable insights to inform policymakers, public administrators, and stakeholders in effectively navigating the challenges associated with AI adoption. By providing a detailed analysis of the advantages and potential challenges, and by suggesting effective implementation strategies, the study seeks to improve governance practices in the digital era, promoting fairness and inclusivity.